MASALAH TRANSPORTASI MULTI-OBJEKTIF FUZZY DUA TAHAP - , TEGUH RIZALI ZAHRONI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis was discussed about multi-objective transportation problem which is supply and demand were given in trapezium fuzzy number. Due to the unable of storage to receive the quantity of minimum demand on once shipment, then the shipment was implemented in two stage. Fuzzy geometric programming approach is used to determine the pareto solution of multi-objective fuzzy two stage transportation problem. The whole of pareto solution is sum of pareto solution first stage with pareto solution second stage.